Evidence for the complex relationship between free amino acid and sugar concentrations and acrylamide‐forming potential in potato. (23rd January 2014) - Muttucumaru, N.; Powers, S.J.; Elmore, J.S.; Briddon, A.; Mottram, D.S.; Halford, N.G.
Abstract Free amino acids and reducing sugars participate in the Maillard reaction during high‐temperature cooking and processing. This results not only in the formation of colour, aroma and flavour compounds, but also undesirable contaminants, including acrylamide, which forms when the amino acid that participates in the reaction is asparagine. In this study, tubers of 13 varieties of potato (Solanum tuberosum), which had been produced in a field trial in 2010 and sampled immediately after harvest or after storage for 6 months, were analysed to show the relationship between the concentrations of free asparagine, other free amino acids, sugars and acrylamide‐forming potential. The varieties comprised five that are normally used for crisping, seven that are used for French fry production and one that is used for boiling. Acrylamide formation was measured in heated flour, and correlated with glucose and fructose concentration. In French fry varieties, which contain higher concentrations of sugars, acrylamide formation also correlated with free asparagine concentration, demonstrating the complex relationship between precursor concentration and acrylamide‐forming potential in potato. Storage of the potatoes for 6 months at 9°C had a significant, variety‐dependent impact on sugar and amino acid concentrations and acrylamide‐forming potential.